Body and testicular biometric parameters of the scorpion mud turtle (Kinosternon scorpioides) (Acta Scientiarum. Biological Sciences, 2014)
The reptile Kinosternon scorpioides is a freshwater chelonian, popularly known as jurará, and is found in the Baixada Maranhense, Maranhão State, Brazil. Due to the lack of scientific information on the reproductive biology of the species, current paper describes the body and testicular biometry and the gonad-somatic index (GSI) in adult specimens collected from the natural environment. Twenty male adults were collected in the rainy (n = 10) and dry (n = 10) seasons. Data were derived from the body, testis size and GSI and tests of correlation between these measures were performed. The body biometrics of free-living Kinosternon scorpioides is similar to those found in other studies for adult animals bred in captivity. The body weight was higher in animals collected in the rainy season than that in animals collected in the dry season. The testis size presents variations among animals captured during the rainy and dry season, but the gonadossomatic index did not vary between different groups of animals. Further studies were suggested related to the levels of sexual steroid hormones and behavioral studies to understand the factors related to the species´s reproductive cycle.